1980
DOI: 10.1080/00021369.1980.10864432
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Acetic Acid Bacteria for Submerged Acetic Acid Fermentation at High Temperature

Abstract: Industrial vinegar production by submerged acetic acid fermentation has been carried out using Acetobacter strains at about 30°C. To obtain strains suitable for acetic acid fermentation at higher temperature, about 1,100 strains of acetic acid bacteria were isolated from vinegar mash, soils in vinegar factories and fruits, and their activities to oxidize ethanol at high temperature were examined. One of these strains, No. 1023, identified as Acetobacter aceti, retained full activity to produce acetic acid in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 1 publication
0
22
0
1
Order By: Relevance
“…The concentration of acetic acid was measured by titration with 1 N NaOH as described by Ohmori et al (15 ability of each strain thus obtained was determined by measuring the production of acetic acid as described by Ohmori et al (16). The resistance to acetic acid was determined by the method described by Ohmori et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of acetic acid was measured by titration with 1 N NaOH as described by Ohmori et al (15 ability of each strain thus obtained was determined by measuring the production of acetic acid as described by Ohmori et al (16). The resistance to acetic acid was determined by the method described by Ohmori et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the genetic instability in ethanol oxidation in Acetobacter spp., spontaneous mutations resulting in deficiency in acetic acid resistance (Ohmori et al, 1980) and cellulose formation (Cook & Colvin, 1980;Steel & Walker, 1957) arise at high frequencies. Investigations have revealed that insertion sequences, such as IS1031s (from 1S1031A to IS1031D) and 19032, participate in the inactivation of several genes (Coucheron, 1991(Coucheron, , 1993Iversen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the genetic background of the terminal oxidase in ethanol oxidation, we first purified and characterized the terminal oxidase from a thermotolerant strain, A. aceti 1023 (24), a suitable strain for submerged acetic acid fermentation. We then cloned and characterized the gene cluster * Corresponding author.…”
mentioning
confidence: 99%